Simplify the expression: –7c2–c2+–5c2–2c2+8c2–9c2

Question

Simplify the expression:
–7c2–c2+–5c2–2c2+8c2–9c2

in progress 0
Thông Đạt 7 months 2021-08-02T07:57:59+00:00 2 Answers 4 views 0

Answers ( )

    0
    2021-08-02T07:59:38+00:00

    i would start by grouping them into sections because they’re all like terms.
    (-7c2-c2) = -8c2
    (-5c2-2c2)= -7c2
    (8c2-9c2) =-c2
    then add them all together.
    -8c2-7c2-c2
    since they’re all negative you can add them together but don’t forget the negative.
    8+7=15
    15+1 = 16
    add the negative back in to get -16c2

    0
    2021-08-02T07:59:56+00:00

    Answer:

    the answer is why is math so hard

    Step-by-step explanation:

    Duh

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )